Alberta Family Integrated Care™ and Standard Care: A Qualitative Study of Mothers' Experiences of their Journeying to Home from the Neonatal Intensive Care Unit - Rachael Dien; Karen M. Benzies; Pilar Zanoni; Jana Kurilova (SAGE Publishing, 2022)
Globally, one in ten infants is born preterm. Most preterm infants require care in a level II Neonatal Intensive Care Unit (NICU), which are highly technological critical care environments that can be overwhelming for parents. Alberta Family Integrated Care (AB-FICare™) is an approach to care that provides strategies to integrate parents into their infant's care team. This sub-study is the first to compare mothers' experiences in the context of AB-FICare™ and standard care. Semi-structured interviews with mothers from AB-FICare™ ( n = 14) and standard care ( n = 12) NICUs were analyzed using interpretive description informed by grounded theory methods. We identified a major theme of Journeying to Home with six categories: Recovering from Birth, Adapting to the NICU, Caring for Baby, Coping with Daily Disruption, Seeing Progress, and Supporting Parenting. Mothers in the AB-FICare™ group identified an enhancement to standard care related to building reciprocal trust with healthcare providers that accelerated Journeying to Home.